PENGEMBANGAN VARIASI LATIHAN DAYA TAHAN OTOT TUNGKAI UNTUK ATLET BOLAVOLI - Hariyanti, Hariyanti (Performance, 2020)
The research aims to develop a variety of leg muscle endurance exercises in volleyball. This research method is Research and Development (R&D). The subject involved 14 volleyball athletes at the Gajayana Club in Malang. Data collection in the form of observation, interviews and questionnaires. This research has gone through two validations of volleyball training experts obtained 91.25% results, small group test results obtained 90%, large group test results obtained by 96%. The results of the study concluded that variations in leg muscle endurance exercises were very valid and could be applied to the volleyball athletes of Club V3 Gajayana Malang.